2000
DOI: 10.1016/s1044-0305(00)00134-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline: A conductive polymer coating for durable nanospray emitters

Abstract: Despite the tremendous sensitivity and lower sample requirements for nanospray vs. conventional electrospray, metallized nanospray emitters have suffered from one of two problems: low mechanical stability (leading to emitter failure) or lengthy, tedious production methods. Here, we describe a simple alternative to metallized tips using polyaniline (PANI), a synthetic polymer well known for its high conductivity, anticorrosion properties, antistatic properties, and mechanical stability. A simple method for coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 28 publications
0
76
0
Order By: Relevance
“…In this type of interface, electrical contact is established in several ways: (i) a conductive capillary tip is obtained by coating the capillary outlet with a metal usually silver [6], gold [7] or polymers [8] providing electrical contact at the border between a capillary tip and the sprayer tip;…”
Section: Sheathless Interfacementioning
confidence: 99%
“…In this type of interface, electrical contact is established in several ways: (i) a conductive capillary tip is obtained by coating the capillary outlet with a metal usually silver [6], gold [7] or polymers [8] providing electrical contact at the border between a capillary tip and the sprayer tip;…”
Section: Sheathless Interfacementioning
confidence: 99%
“…The emitters were prepared by pulling heated glass capillaries with the Sutter Instrument Co. P-2000 laser-based micropipette puller as described previously [50,51]. The emitters were pulled to fine open-ended tapers ranging from 1 to 5 m and coated by polyaniline (PANI) (Monsanto, St. Louis, MO) to provide conductivity needed for nanospray [52]. Previous results have shown that pulling of borosilicate glass by a laser-based micropipette puller can result in reproducible performance by mass spectrometry for different emitters created using the same pulling program protocol [51].…”
Section: Emitter Fabricationmentioning
confidence: 99%
“…Regardless of some processing problems, this polymer has already found numerous applications in different fields. Among the others, it should be mentioned such technologies like electromagnetic shielding [4], conductive coatings [5], corrosion protection [6], artificial muscles [7], light-emitting diodes [8], field-effect transistors [9], photovoltaic cells [10] and sensors [11]. Polyaniline also can be used as an efficient catalyst in chemical technology, or as a catalyst substrate [12].…”
Section: Introductionmentioning
confidence: 99%